Biological Barriers for Drug Delivery and Development of Innovative Therapeutic Approaches in HIV, Pancreatic Cancer, and Hemophilia A/B - Emre Basar; Henry Mead; Bennett Shum; Ingrid Rauter; Cihan Ay; Adriane Skaletz-Rorowski; Norbert H. Brockmeyer (MDPI AG, 2024)
Biological barriers remain a major obstacle for the development of innovative therapeutics. Depending on a disease's pathophysiology, the involved tissues, cell populations, and cellular components, drugs often have to overcome several biological barriers to reach their target cells and become effective in a specific cellular compartment. Human biological barriers are incredibly diverse and include multiple layers of protection and obstruction. Importantly, biological barriers are not only found at the organ/tissue level, but also include cellular structures such as the outer plasma membrane, the endolysosomal machinery, and the nuclear envelope. Nowadays, clinicians have access to a broad arsenal of therapeutics ranging from chemically synthesized small molecules, biologicals including recombinant proteins (such as monoclonal antibodies and hormones), nucleic-acid-based therapeutics, and antibody-drug conjugates (ADCs), to modern viral-vector-mediated gene therapy. In the past decade, the therapeutic landscape has been changing rapidly, giving rise to a multitude of innovative therapy approaches. In 2018, the FDA approval of patisiran paved the way for small interfering RNAs (siRNAs) to become a novel class of nucleic-acid-based therapeutics, which-upon effective drug delivery to their target cells-allow to elegantly regulate the post-transcriptional gene expression. The recent approvals of valoctocogene roxaparvovec and etranacogene dezaparvovec for the treatment of hemophilia A and B, respectively, mark the breakthrough of viral-vector-based gene therapy as a new tool to cure disease. A multitude of highly innovative medicines and drug delivery methods including mRNA-based cancer vaccines and exosome-targeted therapy is on the verge of entering the market and changing the treatment landscape for a broad range of conditions. In this review, we provide insights into three different disease entities, which are clinically, scientifically, and socioeconomically impactful and have given rise to many technological advancements: acquired immunodeficiency syndrome (AIDS) as a predominant infectious disease, pancreatic carcinoma as one of the most lethal solid cancers, and hemophilia A/B as a hereditary genetic disorder. Our primary objective is to highlight the overarching principles of biological barriers that can be identified across different disease areas. Our second goal is to showcase which therapeutic approaches designed to cross disease-specific biological barriers have been promising in effectively treating disease. In this context, we will exemplify how the right selection of the drug category and delivery vehicle, mode of administration, and therapeutic target(s) can help overcome various biological barriers to prevent, treat, and cure disease.